Resistance : Jews and Christians who defied the Nazi terror - Tec, Nechama 1931- (Oxford Univ. Press, 2013)
Introduction: "at the edge of nowhere" -- Learning how to oppose -- The ghettos -- The forests -- The concentration camps -- The couriers -- The special case of Jan Karski -- Conclusion: "not alone